Effects of aging on memory strategies: a validation of the Portuguese version of the Test of Memory Strategies. (30th November 2018) - Fernandes, Sara M.; Araújo, Alexandra M.; Vázquez-Justo, Enrique; Pereira, Carolina; Silva, Ana; Paul, Nuria; Yubero, Raquel; Maestú, Fernando
Abstract: Objective : Previous literature has shown that executive functions (EF) are related to performance in memory tasks. The fact that there are no psychometric tests that evaluate these two constructs simultaneously led a group of researchers to develop the Test of Memory Strategies (TSM). Given the potential importance of this instrument for neuropsychological evaluation, in this study, we aimed to evaluate the psychometric properties of the TMS in Portuguese sample. We also examined the effect of aging by exploring profiles of performance on the TMS, comparing young and elderly healthy subjects.Method : Total of 135 healthy participants were submitted to a neuropsychological assessment and were divided into four age groups: a group of young adults (25–35 years) and three groups of older individuals (aged 60–69 years, 70–79 years, and 80 or more years).Results : Findings supported the reliability of the TMS scores, based on analyses of internal consistency. As expected, factor analysis of the TMS scores revealed that the test yielded two factors, one capturing EF and the other memory. Correlations with classic neuropsychological tests supported convergent and discriminant validity of the TMS scores. The elderly groups presented more difficulties in creating and mobilizing memory strategies when compared with a younger group, after controlling for the influence of education, although both groups presented increases in performance throughout the five TMS subscales.Conclusions : The findings suggest that the TMS is an adequate measure to assess memory and EF, simultaneously, presenting adequate psychometric properties for a Portuguese sample.